Characterization and Synthesis of Some α, β-unsaturated Ester Derivatives from Aliphatic Aldehydes - Bari, M. A.; Karim, M.M.; Hoque, M. M.; Miah, M. A. J. (Journal of Scientific Research, 2010)
Ethyl diazoacetate compound is useful synthetic intermediates for α, β-unsaturated ester in organic synthesis but, due to its toxicity and unpredictable explosive behaviour, its unique reactivity has not been fully exploited and the use on large scale has been avoided. We have developed a reliable method that generates EDA compound in situ. Our approach is based on the Wittig reaction, which utilizes EDA as diazo precursors. In the presence of Cu(OTf)2, we found that diazo compounds can be cleanly converted to alkenyl compounds under mild reaction conditions and in a narrow range of solvents. These diazo compounds can then be induced to react directly with aldehydes to synthesize olefin. We have shown the usefulness of this chemistry in a number of different transformations, such as Wittig olefination reactions chemistry as applied toward the synthesis of more complicated molecules. <span style="font-size: 6pt; color: #000000; letter-spacing: -0.15pt; mso-bidi-font-size: 9.0pt; mso-bidi-font-weight: bold; mso-bidi-font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 0pt;"> Keywords: α, β-unsaturated ester; Acryclic acid ethyl ester; Aliphatic aldehyde; Cu(II) triflate; Triphenylphosphine. © 2010 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v2i2.4167 J. Sci. Res. 2 (2), 343-350 (2010)